Terms of (Be)longing: Queerying the Trace and Embrace of Print Media - Nicholas, Luca (Auckland University of Technology, 2020)
My project uses methods of intaglio, screenprinting, sculpture, and installation to explore the loss of home and belonging for queer subjects. - Home is a space that is often layered with heteropatriarchal and neoliberal capitalist ideas of ‘success’— ideas that do not easily fit queer bodies. When queer people gain access to dominant spaces of belonging, it is often a process that is contingent on assimilating to these hegemonic ideals. The visibility of queer experience therefore risks becoming commodified by governing bodies of power that reinforce essentialist regimes between gay and straight, self and other. Accordingly, this project explores how terms of belonging can privilege queer experiences as by us, and for us. My research queeries the contingencies of queer belonging by shifting trauma, distress, and disorientation into generative artworks that are driven by pathos, humour, and care. I enact this queerying through implicit methods of touch, embrace, and trace that are associated with printmaking. These methods offer queer bodies privacy and care. My research takes the position that queer artists and their experiences should not be beholden to a status of educator, or a form of representation that hinges upon expressing trauma to validate both their practices and experiences. My methods reveal how the accumulation of embrace and trace in print-based media, sculpture, and installation can be used to present more affirmative and caring models of belonging for queer bodies.
Keywords: Queer; Printmaking; Belonging; Care; Home